Complaints of Computer Vision Syndrome in Telemarketing Workers at Bank X in Jakarta - Nanda Waskito Nugroho; Mona Lestari; Anita Camelia; Desheila Andarini; Amrina Rosyada; Rizka Faliria Nandini; Poppy Fujianti (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Computer Vision Syndrome (CVS) or digital eye strain is a collection of eye problems related to vision. The telemarketing division in Bank X has 10 hours working time per day and 60 hours per week. This study aimed to determine CVS complaints among telemarketing workers and analyze the factors that caused CVS complaints in workers. Methods: The study used a cross-sectional study design, with a total sample of 53 workers. The variables studied were lighting intensity, monitor distance, age, refractive disorders, eye rest, and eye protection. The study used a lux meter to measure the light intensity and the Snellen chart to see eye refraction abnormalities. Results: The results determined that 77.4% of computer workers in Bank X Telemarketing division experienced CVS complaints while 22.6% did not experience CVS. The results of statistical tests showed that light intensity, monitor distance, refractive disorders, and eye rest were associated with CVS complaints, while age and eye protection equipment were not related to CVS complaints. Conclusion: Most telemarketing workers experienced CVS complaints caused by lighting intensity, monitor distance, refractive disorders, and eye rest.